The Influence of Various Adhesive Systems and Polishing Methods on Enamel Surface Roughness after Debonding of Orthodontic Brackets: A Three-Dimensional In Vitro Evaluation - Křivková, Tereza; Tichý, Antonín; Tycová, Hana; Kučera, Josef (Materials, 2023)
A slight alteration of the enamel surface is inevitable upon debonding of orthodontic brackets, adhesive removal, and finishing/polishing. The aim of this in vitro study was to compare two adhesives and three polishing methods by measuring enamel surface roughness using confocal laser scanning microscopy (CLSM). Brackets were bonded on 42 extracted human premolars using Transbond XT (Transbond group) or Fuji Ortho (Fuji group). After debracketing, adhesives were removed with a tungsten carbide bur, and surfaces were polished using Sof-Lex discs, a rotary brush with a prophylactic paste (Depural), or a prophylactic cup with two polishing pastes (n = 7 in each subgroup). Surface roughness (Sa, Sku, Sq, and Sz) was measured using CLSM and compared before treatment (T1), after debracketing and adhesive removal (T2), and after polishing (T3). The data were statistically analyzed using the Mann-Whitney U and Kruskal-Wallis tests with Bonferroni correction. The time required for adhesive removal was measured and compared using a two-sample t-test. Surface roughness at T2 increased compared to T1, but the difference was significant only for the Fuji group (p < 0.01). The time required to remove Transbond XT (94.1 ± 6.8 s) was significantly higher compared to Fuji (72.1 ± 5.9 s, p < 0.0001). Polishing with Sof-Lex discs resulted in lower surface roughness compared to T1 (p = 0.018). Using Depural and polishing pastes showed no significant difference in surface roughness compared to T1, except for a significant decrease in Sa and Sq for Transbond (p = 0.043) and in Sku for Fuji (p = 0.018) after polishing with Depural. In conclusion, the removal of Transbond took significantly longer, but there were fewer residues of composite resin on the enamel surface. Sof-Lex discs decreased enamel roughness, whereas enamel morphology and roughness were similar to the pre-treatment state after polishing with polishing pastes.